The Influence Good Corporate Governance Index, Earning Management on Firm Value Empirical studies on real eastate property companies listed on stock exchanges in Indonesia 2009-2012 - Maidefrison '; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research is to examine the effect of Good Corporate Governance index and Earnings Management on firm value in property real estate that listed in Indonesian stock exchanges(BEI) 2009 until 2012.The purposive sampling method is used to determine our samplengs . From ninety-nine firms, we got thirty-one firms. To analysis the data we use multiple regression analysis. T-test, F-test, and determine koefisien are use to examine our hypothesis. The result shows that mean why good corporate governance index significany positive affect on firm value and earnings management has not significant negative effect on the firm value.Keywords: Good Corporate Governance, Earnings Management and firm Value